Geriatric Trauma Mortality: Does Trauma Center Level Matter?. Issue 12 (December 2021) - Rogers, Frederick B.; Morgan, Madison E.; Brown, Catherine Ting; Vernon, Tawnya M.; Bresz, Kellie E.; Cook, Alan D.; Malat, Jaclyn; Sohail, Neelofer; Bradburn, Eric H.
Background: Given their mostly rural/suburban locations, level II trauma centers (TCs) may offer greater exposure to and experience in managing geriatric trauma patients. We hypothesized that geriatric patients would have improved outcomes at level II TCs compared to level I TCs. Methods: The Pennsylvania Trauma Outcome Study (PTOS) database was retrospectively queried from 2003 to 2017 for geriatric (age ≥65 years) trauma patients admitted to level I and II TCs in Pennsylvania. Patient demographics, injury severity, and clinical outcomes were compared to assess differences in care between level I and II TCs. A multivariate logistic regression model assessed the adjusted impact of care at level I vs II TCs on mortality, complications, and functional status at discharge (FSD). The National Trauma Data Bank (NTDB) was retrospectively queried for geriatric (age ≥65 years) trauma admissions to state-accredited level I or level II TCs in 2013. Results: 112 648 patients met inclusion criteria. The proportion of geriatric trauma patients across level I and level II TCs were determined to be 29.1% and 36.2% ( P <.001), respectively. In adjusted analysis, there was no difference in mortality (adjusted odds ratio [AOR]: 1.13; P = .375), complications (AOR: 1.25; P = .080) or FSD (AOR: 1.09; P = .493) when comparing level I to level II TCs. Adjusted analysis from the NTDB (n = 144 622) also found that mortality was not associated with TC level (AOR: 1.04; P = .182). Discussion: Level I and level II TCs had similar rates of mortality, complications, and functional outcomes despite a higher proportion (but lower absolute number) of geriatric patients being admitted to level II TCs. Future consideration for location of centers of excellence in geriatric trauma should include both level I and II TCs.